PENGGUNAAN METODE PROBLEM BASED LEARNING (PBL) DENGAN STRATEGI (THINK TALK WRITE) UNTUK MENINGKATKAN KEMAMPUAN PENGGUNAAN KALIMAT EFEKTIF PADA TEKS BERITA - Siti Mafiyatul Hasanah (Universitas Wijaya Kusuma Surabaya, 2023)
Problem Based Learning Learning Model Using Think Talk Write strategy and Power Point Media can be used to improve the ability to use effective sentences in news item text because the model, strategy, and media provide ideas to students to find and start news item text writing activities by paying attention to the use of effective sentences. The improvement of writing activities by paying attention to the use of effective sentences in the news item text can be seen from anthusiasm of the students and the writings they had created.